Open Filters and Congruence Relations on Self-Distributive Weak Heyting Algebras - Mohsen Nourany; Shokoofeh Ghorbani; Arsham Borumand Saeid (Bulletin of the Section of Logic)
In this paper, we study (open) filters and deductive systems of self-distributive weak Heyting algebras (SDWH-algebras) and obtain some results which determine the relationship between them. We show that the variety of SDWH-algebras is not weakly regular and every open filter is the kernel of at least one congruence relation. Finally, we characterize those SDWH-algebras which are weakly regular by using some properties involving principal congruence relations.